VILLAGE-OWNED ENTERPRISES (BUMDES) AS A COLLABORATIVE MODEL ENVIRONMENTAL MANAGEMENT - Jagad Aditya Dewantara; Efriani Efriani; La Ode Topo Jers; Wibowo Heru Prasetiyo; Sulistyarini Sulistyarini (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2021)
Some peatland management cases, particularly in Kalimantan, cause serious environmental problems, especially in flammable land. Local people around the area are the first to receive the impacts. Therefore, peatland management needs to be prudent and requires sustainable environmental management. This study aims to find a model for peatland management carried out by the government and local communities through BUMDes program. According to the interview results and field observations, peatland management with a collaborative model between the government (state) and the local community in Rasau Jaya Village is found in the form of Maju Jaya Village-owned Enterprises (BUMDes). This research includes planning, utilization, management, and supervision of the peatland area. The government provides funds and legality, while the local communities carry out peatland utilization, management, and maintenance through mutual cooperation culture. In this study, peatland functions as a tourist attraction managed by the local community (ecotourism). Real implementation government collaboration with the local community has opened up new livelihoods for communities without undermining peatlands' ecological ecosystem.